PHYSIOTHERAPISTS BARRIERS OF DELIVERING CARDIOPULMONARY REHABILITATION FOR PATIENTS WITH HEART FAILURE: A CROSS-SECTIONAL STUDY - Dr. Aisha Ijlal; Dr. Hajra Kanwal; Dr. Warda Farooq; Dr. Shafiat Jalalani; Dr. Talha Iqbal; Dr. Nida Waheed; Dr. Syed Uzair Mahmood; Dr. Aqsa Faiz (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Heart Failure (HF) poses a significant global health burden, necessitating effective management strategies like Cardiac Rehabilitation (CR) programs. However, low participation rates persist due to various barriers, highlighting the need for understanding physiotherapists perspectives to improve CR utilization. This study aims to assess physiotherapists perceptions of CR and identify barriers they face in providing CR to HF patients in Pakistan. A cross-sectional study involving 200 physiotherapists in Pakistan was conducted, utilizing a questionnaire to assess their perceptions of CR, preferred delivery methods, perceived barriers, and factors influencing referral decisions. Findings reveal that 88% of physiotherapists believe CR improves fitness, with 75% acknowledging its effectiveness in reducing breathlessness. They prefer hospital-supervised programs (75%) focusing on weight and stress management and medication information. Factors influencing CR referrals include low exercise tolerance (80%), patient education (78%), declining activity levels (77%), fatigue (71%), and breathlessness-related mobility issues (70%). Common barriers to CR referrals include lack of standardized protocols (73%), patient refusal and skepticism (73%), limited CR center availability (71%), and shortage of experienced staff (71%). Despite positive perceptions of CR, barriers such as standardized referral protocols, limited center availability, and staff shortages hinder its utilization. Addressing these challenges could enhance CR participation, improve patient outcomes, and mitigate the HF burden in Pakistan.